QUALITY LEGAL EDUCATION AND THE PROHIBITION OF DISTANCE LEARNING IN LAW DEGREE PROGRAMS IN BRAZIL (REMUNOM, 2026)
This article examines the normative, pedagogical, and institutional foundations supporting the prohibition of distance learning in undergraduate law programs in Brazil, considering Decree No. 12,456/2025 and the National Curricular Guidelines established by MEC Resolution No. 5/2018. The study adopts a qualitative approach, employing bibliographic research and documentary analysis of legal norms, educational policies, and institutional positions. The findings indicate that the requirement for in-person legal education is directly linked to the development of theoretical, practical, and socio-emotional competencies essential for legal practice, as well as to the humanistic and critical training demanded by the Brazilian educational framework. Face-to-face interaction is shown to enhance legal reasoning, analytical skills, oral advocacy, and conflict resolution, which are central elements of professional legal training. The study concludes that the prohibition of distance learning in law programs functions as a regulatory mechanism aimed at safeguarding the quality of legal education, aligning with national educational guidelines and Brazil’s commitment to Sustainable Development Goal 4, which promotes inclusive, equitable, and quality education.